Enhancing the Quality of Public Service One-Stop Integrated Services (PTSP) at the Bekasi Class 1A Special District Court - Hermalia, Jihan Ananda; Takrim, Muhammad (West Science Business and Management, 2025)
The development of digital technology makes it easier to provide more efficient and transparent services. This study was conducted with the aim of knowing the application of the quality of one-stop integrated services at the Bekasi Class 1A Special District Court in improving services to the community. The method used in this study is qualitative, using observation methods, interviews with the head of the General Subdivision. The results of the analysis obtained show that the application of service quality runs the service process in accordance with the dimensions of public service, which consists of tangible shows that the physical facilities of PTSP meet public service standards. Reliability shows that the apparatus has been polite and attentive, listening to complaints, and trying to provide quick and appropriate solutions, responsiveness shows that consistency in following standard operating procedures and providing consistent and reliable services. Assurance shows that the apparatus has responded quickly to community requests and problems. Empathy shows that public complaints can be taken more seriously with a good complaint system. The findings and obstacles are that there is no electronic digital-based suggestion box such as Google Form which can be accessed via Smartphone. Therefore, the solution provided is to create an online-based suggestion box, namely Google Form, to make it more efficient in providing services.